The Intrinsic Nature of Persulfate Activation and N-Doping in Carbocatalysis - Ren, Wei; Nie, Gang; Zhou, Peng; Zhang, Hui; Duan, Xiaoguang; Wang, Shaobin (Environmental science & technology, 2020)
Persulfates activation by carbon nanotubes (CNT) has been evidenced as nonradical systems for oxidation of organic pollutants. Peroxymonosulfate (PMS) and peroxydisulfate (PDS) possess discrepant atomic structures and redox potentials, while the nature of their distinct behaviors in carbocatalytic activation has not been investigated. Herein, we illustrated that the roles of nitrogen species in CNT-based persulfate systems are intrinsically different. In PMS activation mediated by nitrogen-doped CNT (N-CNT), surface chemical modification (N-doping) can profoundly promote the adsorption quantity of PMS, consequently elevate potential of derived nonradical N-CNT-PMS* complexes, and boost organic oxidation efficiency via an electron-transfer regime. In contrast, PDS adsorption was not enhanced upon incorporating N into CNT due to the limited equilibrium adsorption quantity of PDS, leading to a relatively lower oxidative potential of PDS/N-CNT system and a mediocre degradation rate. However, with equivalent persulfate adsorption on N-CNT at a low quantity, PDS/N-CNT exhibited a stronger oxidizing capacity than PMS/N-CNT because of the intrinsic higher redox potential of PDS than PMS. The oxidation rates of the two systems were in great linearity with the potentials of carbon-persulfate* complexes, suggesting N-CNT activation of PMS and PDS shared the similar electron-transfer oxidation mechanism. Therefore, this study provides new insights into the intrinsic roles of heteroatom doping in nanocarbons for persulfates activation and unveils the principles for a rational design of reaction-oriented carbocatalysts for persulfate-based advanced oxidation processes.